Umetna inteligenca v zdravstvu in farmaciji - Baťková, Anna (Farmacevtski vestnik, 2021)
Advances in computing power and digitalisation of data have enabled the development of artificial intelligence, which has also begun to change the healthcare system. It brings possible solutions and improvements in many areas of healthcare and pharmacy, but also challenges that will need to be addressed. The use of artificial intelligence-based systems is also changing the way healthcare professionals work, transforming the necessary knowledge and interest.
Keywords: digitalna revolucija; farmacevtska skrb; Umetna inteligenca; Zdravstvo